EVIDENCE OF ANTI-GOUT ACTIVITY OF A STANDARDIZED TRADITIONAL HERBAL MEDICINE - A. Shaukat; K. Hussain; N. I. Bukhari; N. Shehzadi; S. Naheed; S. Siddique; F. Saghir; S. Iftikhar (Journal of Animal and Plant Sciences, 2021)
A five-herb containing traditional homemade medicine is extensively used to treat gout but the literature is devoid of scientific evidence. Therefore, the present study aimed to investigate anti-gout and anti-inflammatory activities of a standardized traditional medicine. Reversed phase HPLC method was developed for the simultaneous determination of chlorogenic acid, caffeic acid, vanillin and ferulic acid, and applied to standardize the traditional medicine. Completely randomized design (CRD) was followed in the current study. In vivo anti-gout activity was evaluated using potassium oxonate induced hyperuricemia model and the study was divided into two parts, protective and curative study. In former, male Wistar rats were randomly segregated into 4 groups (n=6) and treated for 21 days while in later, rats from toxic group were randomly segregated into 3 groups (n=3), two treated and one control, and treatment was continued for 7 days. Serum uric acid level, xanthine oxidase activity of rat-liver homogenate and renal histopathology were used to assess anti-gout activity. The medicine was also evaluated for anti-inflammatory activity using carrageenan induced hind paw edema model. Data were analyzed by one-way ANOVA, and a p value ≤ 0.05 was regarded as significantly different. The medicine contained 0.2967 mg/g chlorogenic acid, 0.2698 mg/g caffeic acid, 0.2122 mg/g vanillin and 0.2160 mg/g ferulic acid. The medicine significantly reduced uric acid level in medicine-treated groups in both protective and curative studies (p≤0.05). The medicine also exhibited significant xanthine oxidase inhibition in rat-liver homogenate in protective and curative study (p≤0.05). Kidney histopathological examination indicated mild interstitial cells infiltration in treatment groups as compared to toxic group. The medicine also exhibited significant anti-inflammatory activity indicated by 49.8% reduction of paw edema volume (p≤0.05). The findings of this study support the traditional use of the herbal medicine, and the developed HPLC method may be useful to produce standardized anti-gout medicine.
Keywords: Gout; HPLC; standardization; polyherbal; xanthine oxidase; potassium oxonate; allopurinol